Effects of mixed wax (beeswax and carnauba wax) on fruit quality and storage life of Vietnamese sweet orange ‘Canh’ during low-temperature storage - N. T. Huyen (2018)
The effect of mixed wax (beeswax and carnauba wax; MW) on postharvest quality and storage life of fruit of Vietnamese sweet orange ‘Canh’ was studied, by coating fruit with 4, 6, 8, 10% MW and then storing the fruit at 5°C for 50 days, while uncoated fruit were stored at 5°C as control. The percentage of weight loss and total sugar, titratable acidity, total soluble solids (TSS) and ascorbic acid content, fruit decay, and rate of respiration were monitored during the storage period. The results showed that 8% MW coating could reduce the percentage of weight loss, rotten fruit, and rate of respiration for 50 days in storage and increase ethanol. Moreover, after 50 days in storage, the 8% MW-coated fruit still maintained their marketable properties, expressed as titratable acidity, TSS content, ascorbic acid, total sugars, and ethanol. For the control fruit at low temperature, the shelf-life was only 40 days.